Social Drama and Constructed Reality in Elections: A Dialectic Reality Analysis of the 5th Debate of 2024 Presidential Election in Indonesia - Yuniar, Ririt; Ahsan, Titania Fattiha; Arifin, Arya Maheswara Putra (Universitas Gadjah Mada, 2024)
Normatively, debates in election is aimed to provide a platform for communicating the idas of candidtaes to the voters. However, in practice what is shown in the floor and screen of debates is often more than this. Based on the comunication theory of dialectic reality, this research aims to understand the social drama and the consturction of reality in the dialectical reality in the 5th presidential debate of the 2024 election in Indonesia, which was shown live in the social media of Indonesian election commitee (KPU), particularly itsYouTube channel. This research is imp[ortant to reveal how the performance displayed causes message distortion, which may shift the focus of the away fromcontent does not reach the public. Using mix method, this research analyzes the process of conveying messages from the costume structure, the content of the debate substance, and the role of new media that displays it. The data present the display of the costumes of the three presidential candidates in the 5th debate, the cirrus of the substance of the debate theme and public comments on the KPU RI YouTube, and the trends of the role of new media. This research conducted the data analysis map ussing Voyant.tools and ytcomment.kmcat.uk/. The results of this study show that First, the costumes of the presidential candidates in the drama of the debate show have elements of representation of cultural and political values. Second, the 5th presidential debate of the 2024 candidates showed a dialectical reality in the form of a stage drama related to the substance of the debate theme (social welfare, culture, education, information technology, health, and employment) with public comments on the YouTube platform. Third, new media has a role in transforming the dialectical reality of the debate event into a social drama in YouTube comments.